Chordoma Of Lumbar Spine - Nirmala M.J.*, H.A. Parshwanath and A.M.Patil (Al Ameen Medical College, 2010)
Chordoma, lesion derived from the notochord, represents about 4% of the primary malignant bone tumours. Males are affected more commonly than females and it is very rare in children;the peak incidence is in the sixth decade of life.The sacrococcygeal region accounts for 50% of cases and the spheno-occipital region or the base of the skull for 37% of cases.The remainder of the cases reported occur in the descending order of frequency in the cervical,thoracic and the lumbar spine.It is found to be rarely involving the lumbar spine(about 2%).We present a case of chordoma involving L4 and L5 vertebral body and disc.The role of epithelial cell marker study has proved a well adjunct to the histopathological diagnosis of chordoma.